Decoding antibody response to MERS-CoV in wild dromedary camels - Faten Idoudi; Ruoke Wang; Long Tian; Ziqing Yang; Kenn Ka-Heng Chik; Peng Chen; Rahma Benabderrazek; Lili Fu; Ruijie Tan; Sayda Dhaouadi; Zakaria Benlasfar; Mahmoud Somia; et al. (Proceedings of the National Academy of Sciences, 2026)
Wild dromedary camels in the Arabian Peninsula and Africa have harbored antibodies against Middle East Respiratory Syndrome Coronavirus (MERS-CoV) for decades, predating zoonotic spillover to humans. However, the potency, specificity, and structural characteristics of these antibodies remain poorly understood. Here, we characterize the antibody responses of naturally infected wild dromedary camels in Tunisia, a MERS-CoV-endemic region. Plasma antibodies from nine camels exhibited variable neutralizing activity, generally increasing with age, and were largely autologous, with minimal cross-reactivity to SARS-CoV-1 or SARS-CoV-2. From a VHH antibody library derived from the peripheral blood mononuclear cells (PBMCs) of a single camel (D17), we identified 34 unique sequences with previously unreported germline origins and unusually long complementarity-determining region 3 (CDR3) sequences. Eight representative VHHs, expressed as human Fc fusions, displayed high-affinity binding to the MERS-CoV receptor-binding domain (RBD) and broad neutralization to RBD mutants (IC 50 : 1.05 to 9.55 ng/mL). Crystal structural analysis revealed distinct neutralization mechanisms: VHH-227 fully blocked DPP4 binding, achieving complete neutralization, while VHH-T71, with partial neutralization (~80%), targeted the RBD core subdomain. This study provides comprehensive characterization of wild dromedary antibody responses, identifying novel nanobodies (Nbs) with broad and potent neutralization to naturally occurring RBD mutants. These findings offer insights into camel immunity and highlight promising candidates for MERS-CoV prophylactic and therapeutic development.